'That degree of isolation is the measure of our appreciation of the great work you are beginning': Trans-Pacific aviation as an opportunity and a challenge. Issue 1 (1st May 2017) - Meaher, Augustine
Pan American World Airways' (Pan Am) decision to establish regular air service between the United States and the South Pacific in the 1930s forced Australia and New Zealand to reconsider their position within the Empire and challenged their understanding of the Asia-Pacific. Technological improvements were outpacing the imperial system. The Pacific was no longer a British lake and America threatened to dominate the new and vital air links so valuable to the isolated Dominions. Furthermore, Pan Am was not prepared to proceed at the slow gentlemanly pace that had previously characterized imperial relations. The opening of the air routes to the South Pacific led to diplomatic and military interests in previously all but ignored atolls and reefs in the South Pacific, which thrust New Zealand into the forefront of imperial relations. New Zealand responded to the opportunities and challenges posed by Pan Am's decision to begin operating a trans-Pacific service with considerable diplomatic finesse and sought to ensure that its own interests were preserved without offending the mother country. Pan Am's operations also challenged Anglo-American relations when at the time Britain could ill-afford to offend Washington. In a period that witnessed the rise of fascism in Europe and an expansionist Japan in Asia, the Royal Navy and the United States Navy were facing off over an uninhabited atoll in the South Pacific. Britain's high-risk diplomatic tactics over Canton Island thus exposed not just a trans-Pacific air link but endangered the Anglo-American relationship and threatened to upset a significant Pacific ally. This article is the first to make use of unrestricted access to the archives of Pan Am and places the establishment of Pan Am's South Pacific operations into an imperial context.